Selecting optimal pharmaceutical excipient formulation from life cycle assessment perspectives: a case study on ibuprofen tablet formulations - Wang, Danping (2022)
Manufacturing of active pharmaceutical ingredients (API) is known to produce significantly larger environmental impacts than manufacturing of commodity chemicals. This prompted the pharmaceutical industry to adopt sustainable manufacturing practices for API synthesis. Environmental impacts of pharmaceutical manufacturing, however, do not end with API synthesis. The API is subsequently formulated with pharmaceutical excipients to form drug dosage for administration, typically in the form of API tablets. Even though pharmaceutical excipients play large indispensable roles in the production and functionality of API tablets, the impacts of excipient selection on the environmental footprints of API tablet production have never been investigated. Herein we performed cradle-to-gate life cycle assessment (LCA) of API tablet production from two different excipient formulations using ibuprofen as the model API. The LCA was performed at each step of the tablet production (i.e. wet granulation, drying, tablet compaction) using inventory data from in-house kilo-scale laboratory experiments. Similar to API synthesis, the results showed that, regardless of the excipient formulation, the environmental impacts of API tablet production were governed by process-level energy consumptions, particularly electricity for drying. Cumulative energy demand of API tablet production was in fact comparable to API synthesis. The importance of the excipient selection was demonstrated through its influence on the process-level energy consumptions. Moreover, production of different excipients left behind varying levels of environmental footprints depending on their raw materials and production processes. The present work established that pharmaceutical excipients and their selection have as big of a role as the API itself in the resultant environmental impacts of oral drug products.